Analysis of raw mixture composition as a factor of increase of portland cement clinker whiteness - Dorogan, Nataliia; Cherniak, Lev (Eastern-European Journal of Enterprise Technologies, 2016)
The newly developed compositions of raw mixtures for clinker production contain minimized amounts of coloring oxides and are controlled by a specially designed computer program CLINKER. The study used various types of enriched carbonate, aluminum- and silica-containing raw materials from different parts of Ukraine to reveal the peculiarities of coagulated structures and phase transformations of dispersions. It has proved that control of the parameters of coagulated structures of slurry dispersions (such as viscosity, fluidity, and kinetic stability) is essential for optimizing raw mixture compositions for wet and combined production of white Portland cement. We have assessed the effect of mineralizing additives necessary to intensify clinker sintering on the characteristics of the slurry coagulated structure and identified the peculiarities of clinker minerals С3S, C2S, C3A, C4AF, and C12A7 that are formed in burning the novel raw mixtures. In addition, we have proved that optical and physical properties of crystalline phases are related to clinker whiteness and traced how burning raw mixtures based on the oxide system CaO–Al2O3–SiO2 results in crystalline phases with a relatively lower refractive index of the optically isotropic and transparent mayenyte C12A7 (Ng=2.85–2.90) as a factor of increasing clinker whiteness. The supplied example shows how to obtain clinker with increased whiteness (80–83 %) by intensifying the synthesis of C12A7, C2AS, and C3A.